O prazer estético e as flores: dispositivos cognitivos e semiótica evolutiva - Kajimoto, Cláudio (2012)
This paper discusses the relationship between the field of Communication and Design, from concepts of biosemiotics and research on aesthetic experience. Studies of communication among living beings, as in Ethology, Biosemiotics and Biomimetics (Bispo, 2004 and Vieira, 2007; also Benyus, 1997) suggest that aesthetic experience, as conceived by the human Umwelt (Kull, 2001), is an adaptive strategy that living systems use in order to survive. This hypothesis is consistent with the proposal that the concept of communication, as well as aesthetic experience, has an objective root. In this context, the latter implies an efficient form of objective organization. Communication among living systems allows their communicative interaction to mold such systems, making them fitted to survive through the production of morphogenesis, among other aspects. As a case study we chose as object the mechanism of communication between flowers and insects, showing how this leads to the evolution and adaptation of such systems (Souza, 1994). If flowers are the reproductive organs of plants, evolutionarily designed to assist in reproduction through the seduction of pollinator insects, why do humans also feel attracted to them, even though we are endowed with a perception and an Umwelt differentiated from those of birds, insects and other animals? We claim that the aesthetic experience with flowers operates in the observer a biological response to the activation of certain cognitive devices we acquire throughout our evolutionary history, and the feeling of pleasure experienced would be associated with the systems of gratification and reward in the brain, pointing to objective qualities of the flower. Thus, we propose the existence of a semiotics capable of organizing natural processes, and a complex system of communication that permeates all living things. In the end, when we unfold the aesthetic strategy of the flowers, we also discover a new way to create and handle design in all its forms and manifestations